2010
DOI: 10.1038/nmeth.1505
|View full text |Cite
|
Sign up to set email alerts
|

Scanless two-photon excitation of channelrhodopsin-2

Abstract: Light-gated ion channels and pumps have made it possible to probe intact neural circuits by manipulating the activity of groups of genetically similar neurons. What is needed now is a method for precisely aiming the stimulating light at single neuronal processes, neurons or groups of neurons. We developed a method that combines generalized phase contrast with temporal focusing (TF-GPC) to shape two-photon excitation for this purpose. The illumination patterns are generated automatically from fluorescence image… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
373
1
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 387 publications
(397 citation statements)
references
References 38 publications
13
373
1
4
Order By: Relevance
“…Integrated with patterned illumination, the system could further be applied for functional excitation [17,28,29,31], 3D fabrication [30], and structured illumination purposes [39][40][41][42]. In this paper, we have demonstrated that the AEC would vary with different patterns at the same single spatial frequency and different orientations, and could reach nearly 29 % difference, e. g., from À11 % to + 18 % with 1.09 mm À1 spatial frequency patterns at the 908 and 08 orientations.…”
Section: Discussionmentioning
confidence: 90%
“…Integrated with patterned illumination, the system could further be applied for functional excitation [17,28,29,31], 3D fabrication [30], and structured illumination purposes [39][40][41][42]. In this paper, we have demonstrated that the AEC would vary with different patterns at the same single spatial frequency and different orientations, and could reach nearly 29 % difference, e. g., from À11 % to + 18 % with 1.09 mm À1 spatial frequency patterns at the 908 and 08 orientations.…”
Section: Discussionmentioning
confidence: 90%
“…Because shift-averaging removes speckle deterministically 28 , and the display's projection rate is 2,000 frames per second, effective patch de-speckling requires only a few milliseconds (2-12 ms in these experiments), allowing for very high effective temporal resolution, which would practically probably be limited by other factors (for example, video processing, hologram computation and optogenetic probe response times). Holographic speckle has emerged as an important issue in the implementation of diffractive photostimulation systems 31 , and it is important to note several alternative designs for circumventing this issue including the use of Generalized Phase Contrast 26 , hybrid holographicmechanical projection systems (that is, rotating diffusers 32 or mechanically vibrated smearing of point patterns 33 ). Other possibilities for speckle reduction are the use of temporally and/ or spatially incoherent light sources.…”
Section: Resultsmentioning
confidence: 99%
“…Diffractive wavefront shaping techniques including computergenerated holography (CGH) and generalized phase contrast are an emerging tool for dynamic patterned photo-excitation [20][21][22][23] that were shown to allow structured two-(2D) and threedimensional (3D) excitation of dendritic arbors 20,24 and neurons 25 using neurotransmitter photolysis as well as twophoton optogenetic stimulation of several neurons in brain slices 26 . The principle advantage of CGH systems 22,23 is that they naturally combine the high intensity, efficiency and resolution that are characteristic of sequential laser deflection methods (such as acousto-optical deflectors) with the capacity for scan-less simultaneous parallel illumination of multiple locations of microdisplay array projectors, but without their respective limitations.…”
mentioning
confidence: 99%
“…Indeed, with adaptive optics we can now image to >400 μm deep into the brain with resolution similar to that normally seen at the superficial depth in brain slices. As a result, adaptive optics would play an important role in the application of many physiological techniques in vivo, such as two-photon uncaging (19), two-photon imaging of dendrites, spines, and axons (20), multiphoton ablation of neuronal structures (21), optogenetic stimulation (22,23), and superresolution imaging (24).…”
Section: Resultsmentioning
confidence: 99%